Impact of Prasugrel and Ticagrelor on Platelet Reactivity in Patients With Acute Coronary Syndrome: A Meta-Analysis - Dai, Lulu; Xu, Jiawei; Jiang, Yuerong; Chen, Keji (Frontiers in Cardiovascular Medicine, 2022)
Background This meta-analysis mainly aimed to compare the impact of prasugrel and ticagrelor on platelet reactivity (PR) in patients with acute coronary syndrome (ACS). Methods We searched four electronic databases to identify randomized controlled trials and cohort studies comparing the impact of prasugrel and ticagrelor on PR in patients with ACS. We performed group analyses according to three detection methods, drug dose [loading dose (LD) and maintenance dose (MTD)] and LD effect time, and assessed the robustness of the results through sensitivity analysis. Results Twenty-five studies with 5,098 patients were eligible. After LD, the incidence of high on-treatment platelet reactivity (HTPR) of ticagrelor was significantly lower than that of prasugrel within 6–18 h based on vasodilator-stimulated phosphoprotein (VASP) test [RR = 0.25 (0.07, 0.85), P = 0.03], there was no significant difference between ticagrelor and prasugrel in the following results: platelets inhibitory effect within 24–48 h based on VerifyNow P2Y12 (VN) assay (P = 0.11) and VASP test (P = 0.20), and the incidence of HTPR within 2–6 h based on VN assay (P = 0.57) and within 24–48 h based on VN assay (P = 0.46) and VASP test (P = 0.72), the incidence of low on-treatment platelet reactivity (LTPR) within 6–18 h based on VASP test (P = 0.46) and 48 h based on VN assay (P = 0.97) and VASP test (P = 0.73). After MTD, the platelet inhibitory effect of ticagrelor was stronger than that of prasugrel based on VN assay [WMD = −41.64 (−47.16, −36.11), P < 0.00001]and VASP test [WMD = −9.10 (−13.88, −4.32), P = 0.0002], the incidence of HTPR of ticagrelor was significantly lower than that of prasugrel based on VN assay [RR = 0.05 (0.02, 0.16), P < 0.00001], the incidence of LTPR of ticagrelor was significantly higher than prasugrel based on VN assay [RR = 6.54 (4.21, 10.14), P < 0.00001] and VASP test [RR = 2.65 (1.78, 3.96), P < 0.00001], the results of Multiple Electrode Aggregometry (MEA) test was inconsistent with the other two detection methods in platelet inhibitory effect and the incidence of HTPR and LTPR. There was no significant difference between ticagrelor and prasugrel in the following clinical outcomes: all-cause death (P = 0.86), cardiovascular death (P = 0.49), myocardial infarction (P = 0.67), stroke (P = 0.51), target vessel revascularization (P = 0.51), stent thrombosis (P = 0.90), TIMI major bleeding (P = 0.86) and bleeding BARC type ≥ 2 (P = 0.77). The risk of bleeding BARC type 1 of ticagrelor was significantly higher than prasugrel [RR = 1.44 (1.03, 2.02), P = 0.03]. Conclusions Compared with prasugrel, ticagrelor might have a stronger platelet inhibition effect, with a lower incidence of HTPR and a higher incidence of LTPR and bleeding BARC type 1, while there might be no significant difference in the risk of thrombosis/ischemic, bleeding BARC Type ≥ 2 and TIMI major bleeding. A higher incidence of LTPR might indicate a higher risk of bleeding BARC type 1. The results of VN assay were consistent with that of VASP test, and not with the MEA test. Systematic Review Registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42022304205, identifier: CRD42022304205.